(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Numerous studies have established the importance of the locus of control in preserving good mental health and adjustment. The current study looked at how adolescents’ loci of control related to their mental health and general adjustment. The participants were 50 female adolescents. The Rotter’s Locus of Control Scale (1966), the Adjustment Inventory for College Students (1995), and the Mental Health Battery (Singh, Gupta, 2000) were also used. Findings: According to the study’s conclusions, adolescent females who have an internal locus of control exhibit better mental health and an overall pattern of adjustment that includes their homes, their relationships with others, their emotions, their education, and their health. This is in contrast to those who have an external locus of control. The study emphasises how internal and external loci of control have a pervasive impact on adolescent females’ mental health and adjustment.